Micro-nano multi-scale high-entropy alloy reinforced titanium-based composite material and preparation method thereof
By using micro-nano multi-scale high-entropy alloys to enhance particles in titanium-based composite materials to form core-shell structures, the problem of low interface bonding strength of traditional titanium-based composite materials is solved, and the strength and strong plasticity of the material are significantly improved.
Patent Information
- Application Number
- CN202510004204.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
In traditional titanium-based composite materials, the thermal expansion coefficients of ceramic or metal glass particles and the titanium matrix have a large difference in thermal expansion coefficient and poor wettability, resulting in low interface bonding strength and weakening the strengthening effect of the reinforcement particles.
Micro-nano multi-scale high-entropy alloy reinforced particles are used to form nano-scale high-entropy alloy reinforced particles through ball milling and current-assisted friction stir processing, and synergistically with micro-scale high-entropy alloy particles to form a core-shell structure to improve interface bonding strength.
The strength and strong plasticity of the material are significantly improved. Through the dispersion distribution of nano-scale particles and the formation of core-shell structure of micro-scale particles, the mechanical properties of the composite material are effectively improved.
Smart Images

Figure CN119794340A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of titanium-based composite material preparation, and specifically relates to a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material and a preparation method thereof. Background Art
[0002] Particle-reinforced titanium-based composites have excellent specific strength, specific stiffness and high temperature resistance, and are widely used in aviation, aerospace, rail transportation and other fields. At present, the reinforcing particles are mainly ceramic particles, metallic glass, etc., but these traditional particles have a large difference in thermal expansion coefficient with the titanium matrix, poor wettability, and low interface bonding strength, which seriously weakens the strengthening effect of the reinforcing particles.
[0003] High entropy alloys are composed of five or more metal elements in approximately equal atomic ratios. Due to their excellent mechanical properties and high temperature resistance, they have gradually become the research focus in the field of composite material reinforcement particles. At present, the common reinforcement particle sizes can be divided into nanometer, submicron and micron levels. If a core-shell structure is formed at the interface after the metal reinforcement particles are combined with the matrix, the mechanical properties of the material can be significantly improved. Theoretically, due to their higher specific surface area, nanoparticles are more likely to react with the matrix at the interface to form a core-shell structure. In addition, nanoparticles can effectively refine the grains and improve the mechanical properties of composite materials by pinning grain growth and providing additional nucleation sites.
[0004] However, due to the high surface energy of nanoparticles, they are prone to agglomeration, resulting in poor uniform dispersion of particles in the matrix, significantly weakening the strengthening effect of the composite material. At the same time, simply adding nanoparticles can easily lead to problems such as difficulty in interface formation and low mechanical properties. Therefore, how to give full play to the advantages of micron and nanoparticles and prepare high-performance titanium-based composite materials has become a problem that needs to be solved. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned problems and provide a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material and a preparation method thereof, wherein micron-level high entropy alloy reinforced particles are transformed into micro-nano multi-scale high entropy alloy reinforced particles, and nano-level high entropy alloy reinforced particles are used for dispersion strengthening distribution to refine the matrix grain size and significantly improve the strength of the material; the micron-level high entropy alloy particles and the matrix form a core-shell structure interface to improve interface bonding, adjust stress distribution, and improve the strength and plasticity of the material.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material, comprising a titanium matrix and micro-nano multi-scale high entropy alloy reinforced particles, wherein the micro-nano multi-scale high entropy alloy reinforced particles include micron-scale high entropy alloy reinforced particles and nano-scale high entropy alloy reinforced particles;
[0008] The micron-sized high entropy alloy reinforcement particles are added through the original powder;
[0009] The nano-scale high entropy alloy reinforcement particles are formed by mechanical crushing during ball milling and current-assisted friction stir processing;
[0010] The micron-sized high entropy alloy reinforcement particles form a continuous and complete interface bond with the titanium matrix, thereby forming a core-shell structure.
[0011] A further improvement of the present invention is that the titanium matrix is one of TA1, TA2 or TA3 industrial pure titanium, and the high entropy alloy reinforcement particles are one of CoCrFeNi, CoCrFeMnNi or AlCoCrFeNi high entropy alloys.
[0012] A further improvement of the present invention is that the particle size distribution range of the titanium matrix and the high entropy alloy reinforcement particles is 13-53 μm, and the purity is ≥99%.
[0013] In a second aspect, the present invention also provides a method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material, comprising the following steps:
[0014] Step 1, weighing a certain weight of titanium matrix powder and high entropy alloy reinforced particle powder, and then placing the two powders in a ball mill for ball milling and mixing to obtain a mixed powder;
[0015] Step 2, using cold isostatic pressing technology to make the mixed powder into a block billet by using a segmented pressurization and pressure holding method, and then using hot isostatic pressing technology to obtain a high-density block billet;
[0016] Step 3: Plastic deformation processing is performed on the dense block billet under a protective atmosphere to obtain a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material.
[0017] A further improvement of the present invention is that the mass fraction ratio of the titanium matrix and the high entropy alloy reinforcement particles is 9:1.
[0018] A further improvement of the present invention is that during the ball milling mixing, the mass ratio of the grinding body to the powder is 3:1 to 10:1, the tank filling rate is 30% to 50%, the rotation speed is 90rpm to 300rpm, and the ball milling time is 3h to 6h.
[0019] A further improvement of the present invention is that the mixed powder is made into a block blank by cold isostatic pressing technology, the sheathing mold material is rubber, and the pressure medium is a liquid mixed with distilled water and emulsion;
[0020] The method of stepwise pressurization and pressure maintenance specifically comprises the following steps:
[0021] Step 1: Apply pressure for 30 seconds, maintain pressure at 30 MPa, add 20 MPa of additional pressure, and hold pressure for 20 minutes;
[0022] Step 2: Pressurization time is 60s, maintaining pressure at 50Mpa, supplementary pressure at 40Mpa, and holding time is 20min;
[0023] Step 3: Pressurize for 90 seconds, maintain pressure at 80 MPa, add 70 MPa, and hold pressure for 20 minutes;
[0024] Step 4: Apply pressure for 120s, maintain pressure at 100Mpa, add pressure at 90Mpa, and hold pressure for 20min.
[0025] A further improvement of the present invention is that the hot isostatic pressing technology uses argon as the pressure transmission medium, the processing temperature is 700-850°C, the working pressure is 100-150Mpa, the insulation time is 2-4 hours, and the cooling rate is 20-50°C / min.
[0026] A further improvement of the present invention is that the protective atmosphere during the current-assisted friction stir processing is argon, the gas working pressure is 0.2-1.0 MPa, the distance between the gas and the center of the processing area is 10-30 mm, and the gas concentration is ≥99%.
[0027] A further improvement of the present invention is that the intense plastic deformation processing of the dense block billet adopts current-assisted stir friction processing technology, wherein the current is direct current, the current source is a high-frequency switching direct current power supply, and the current is 50-200A; during the current-assisted stir friction processing process, the peak temperature range is 873.15K≤T≤1155.15K.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention provides a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material, which synergistically improves the mechanical properties of the composite material by constructing micron-scale and nano-scale multi-scale high entropy alloy particles. Among them, nano-scale particles are dispersed in the titanium matrix, which effectively improves the strength of the material; at the same time, micron-scale and nano-particles can pin the grain boundaries, induce recrystallization, refine the matrix grains, and improve the strength of the matrix. Furthermore, the micron-scale particles can form a continuous and complete interface bond with the titanium matrix, thereby forming a core-shell structure. Among them, when the material is subjected to external force, the inner core of the core-shell structure can effectively absorb the external stress due to its good plasticity, and the shell layer with higher hardness can inhibit the formation and expansion of cracks, thereby significantly enhancing the overall performance of the composite material.
[0030] The present invention also provides a method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material, wherein uniform mixing of titanium powder and high entropy alloy reinforced particles is achieved by ball milling, and then the mixed powder is made into a high-density block blank by cold isostatic pressing + hot isostatic pressing technology, and then the electric-thermal-mechanical coupling characteristics of the current-assisted friction stir processing technology are used to form micro-nano multi-scale high entropy alloy reinforced particles. The advantage of this method is that the ball milling technology and the friction stir processing technology can achieve micron-level particle crushing to form multi-scale micro-nano reinforced particles; at the same time, the uniform distribution of the reinforced particles can be achieved. The current-assisted friction stir processing technology can achieve homogenization, densification and grain refinement of the titanium matrix. In particular, the current-assisted effect can accelerate the movement and annihilation of dislocations through electroplasticity, reduce dislocation density, and improve material plasticity; the Joule heat generated by the current can promote the recrystallization of the matrix and the diffusion of interface elements, and promote the formation of the interface.
[0031] The preparation method of the present invention is suitable for materials that are difficult to plastically process, such as titanium alloys, and belongs to a low-temperature solid-phase processing method, and has the advantages of energy saving, emission reduction, and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings described herein are only for explanation purposes and are not intended to limit the scope of the present invention in any way. In addition, the shapes and proportional dimensions of the various components in the drawings are only schematic, used to help understand the present invention, and are not intended to specifically limit the shapes and proportional dimensions of the various components of the present invention.
[0033] Figure 1 A comparison diagram of uniaxial tensile stress-strain curves of a high entropy alloy reinforced titanium-based composite material prepared in an embodiment of the present invention;
[0034] Figure 2 A comparison diagram of nanoindentation load-displacement curves of high entropy alloy reinforced titanium-based composite materials prepared in an embodiment of the present invention;
[0035] Figure 3 This is the SEM image of Example 1 of the present invention;
[0036] Figure 4 This is the SEM image of Example 2 of the present invention;
[0037] Figure 5 This is the SEM image of Example 3 of the present invention;
[0038] Figure 6 This is the SEM image of Example 4 of the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but it should not be understood that the above subject matter of the present invention is limited to the following embodiments. Without departing from the above technical ideas of the present invention, various substitutions and changes are made according to common technical knowledge and customary means in the field, which should all be included in the protection scope of the present invention.
[0040] The present invention provides a micro-nano multi-scale high-entropy alloy reinforced titanium-based composite material, comprising a titanium matrix and micro-nano multi-scale high-entropy alloy reinforced particles, wherein the micron-sized high-entropy alloy reinforced particles are added through original powder; the nano-sized high-entropy alloy reinforced particles are formed by mechanical crushing during ball milling and current-assisted friction stir processing; the micron-sized high-entropy alloy reinforced particles can form a continuous and complete interface bond with the titanium matrix, thereby forming a core-shell structure.
[0041] As a preferred embodiment, the titanium matrix is one of TA1, TA2 or TA3 industrial pure titanium, and the high entropy alloy reinforcement particles are one of CoCrFeNi, CoCrFeMnNi or AlCoCrFeNi high entropy alloys.
[0042] As a preferred solution, the particle size distribution range of the titanium matrix and the high entropy alloy reinforcement particles is 13-53 μm, and the purity is ≥99%.
[0043] The present invention provides a method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material, comprising the following steps:
[0044] Step 1, weigh a certain weight of titanium matrix powder and high entropy alloy reinforced particle powder so that the mass fraction ratio of the titanium matrix and the high entropy alloy reinforced particles is 9:1, and then place the two powders in a ball mill for ball milling and mixing to obtain a mixed powder, wherein the mass ratio of the grinding body to the powder is 3:1 to 10:1, the tank filling rate is 30% to 50%, the rotation speed is 90rpm to 300rpm, and the ball milling time is 3 to 6h.
[0045] Step 2, using cold isostatic pressing technology to make the mixed powder into a block blank, using rubber as the sheath mold material, and a liquid mixed with distilled water and emulsion as the pressure medium, and then using a segmented pressurization and pressure holding method, specifically including the following steps: Step 1: Pressing time is 30s, maintaining pressure at 30Mpa, supplementing pressure at 20Mpa, and holding pressure time is 20min; Step 2: Pressing time is 60s, maintaining pressure at 50Mpa, supplementing pressure at 40Mpa, and holding pressure time is 20min; Step 3: Pressing time is 90s, maintaining pressure at 80Mpa, supplementing pressure at 70Mpa, and holding pressure time is 20min; Step 4: Pressing time is 120s, maintaining pressure at 100Mpa, supplementing pressure at 90Mpa, and holding pressure time is 20min.
[0046] Step 3, use hot isostatic pressing to further eliminate the pores of the block blank, and use a metal container made of stainless steel to hermetically package the block blank; put the packaged blank into the equipment, and gradually increase the temperature to 700-850°C; at the same time, inject argon into the cavity and apply pressure to 100-150Mpa, and keep the insulation time for 2-4 hours to ensure diffusion bonding between particles and pore closure; after the insulation is completed, reduce the temperature at 20-50°C / min, maintain the pressure relief rate at 1-5MPa / min, and completely release the pressure after cooling to room temperature to obtain a highly dense block blank.
[0047] Step 4, under argon protective atmosphere, set the gas working pressure to 0.2-1.0 MPa, the distance between the gas and the center of the processing area to 10-30 mm, the gas concentration ≥99%, and use current-assisted friction stir processing technology to perform plastic deformation processing on the dense block billet to obtain a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material.
[0048] The current of the current-assisted friction stir processing technology is direct current, and the current source is a high-frequency switching direct current power supply.
[0049] It should be noted that during the current-assisted friction stir processing, excessive heat input will cause the peak temperature of the material to be too high, thereby causing grain coarsening and phase transformation of the titanium matrix, and these changes will have an adverse effect on the mechanical properties of the material. On the contrary, too low a temperature will limit its fluidity due to incomplete plasticization of the material, thereby causing the material to be unable to be fully mixed. Therefore, it is crucial to select appropriate processing parameters to accurately control the heat input. In the present invention, the peak temperature range is 873.15K≤T≤1155.15K during the current-assisted friction stir processing.
[0050] The peak temperature T is calculated by the following formula:
[0051] T=T0+ΔT
[0052] Where, T0 is the temperature of the material caused by the heat generated by the friction between the stirring head and the material, and the unit is K; ΔT is the temperature of the material caused by the heat generated by the Joule heating effect when the current passes through the material, and the unit is K;
[0053] in:
[0054]
[0055] Where, T m is the melting point of the material, in K; ω is the rotation speed, in r / min; υ is the moving speed, in mm / min; K and α are constants, with values of 0.70 and 0.05 respectively;
[0056]
[0057] Where ρ is the resistivity of the material, in Ω·m; j is the current density, in A / m 2 ;t p is the current action time, in seconds; C P is the specific heat capacity of the material, in J / (kg·K); d is the density of the material, in kg / m 3 .
[0058] Example 1
[0059] In this embodiment, pure titanium TA1 is used as the titanium matrix, AlCoCrFeNi is used as the high entropy alloy reinforcement particles, and a micro-nano multi-scale AlCoCrFeNi high entropy alloy reinforced titanium-based composite material with a mass fraction of 10% is prepared. The specific steps are as follows:
[0060] Step 1, weighing a certain weight of pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles, so that the mass fraction ratio of pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles is 9:1, then placing the pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles in a ball mill for ball milling mixing, the mass ratio of the grinding body to the powder is 5:1, the tank filling rate is 40%, the rotation speed is 150rpm, and the ball milling time is 5h to obtain a mixed powder;
[0061] Step 2, using cold isostatic pressing technology to make the mixed powder obtained in step 1 into a block blank with a size of 200mm×100mm×3mm, using a segmented pressurization and pressure-maintaining method.
[0062] Specifically, the first step: the pressure time is 30s, the pressure is maintained at 30Mpa, the additional pressure is 20Mpa, and the pressure holding time is 20min; the second step: the pressure time is 60s, the pressure is maintained at 50Mpa, the additional pressure is 40Mpa, and the pressure holding time is 20min; the third step: the pressure time is 90s, the pressure is maintained at 80Mpa, the additional pressure is 70Mpa, and the pressure holding time is 20min; the fourth step: the pressure time is 120s, the pressure is maintained at 100Mpa, the additional pressure is 90Mpa, and the pressure holding time is 20min;
[0063] Step 3, hot isostatic pressing is used to further eliminate the pores of the block blank obtained in step 2, and a metal container made of stainless steel is used to hermetically package the block blank; the packaged blank is placed in the equipment, and the temperature is gradually increased to 800°C; at the same time, argon is injected into the cavity and the pressure is applied to 100Mpa, and the insulation time is maintained for 2 hours to ensure diffusion bonding between particles and pore closure; after the insulation is completed, the temperature is reduced by 30°C / min, and the pressure relief rate is maintained at 2MPa / min. After cooling to room temperature, the pressure is completely relieved to obtain a highly dense block blank.
[0064] Step 4: In an argon protected atmosphere, the high-density block blank obtained in step 3 is subjected to severe plastic deformation processing by current-assisted friction stir processing technology to obtain a micro-nano multi-scale AlCoCrFeNi high-entropy alloy reinforced titanium-based composite material with a mass fraction of 10%.
[0065] Specifically, the dense block blank prepared in step 3 is placed on the surface of the insulating plate on the table of the current-assisted friction stir processing equipment and fixed with a clamp; one end of the two wires are respectively connected to the positive and negative electrodes of the auxiliary DC power supply equipment, and the other ends are connected to the conductive block of the dense block blank and the conductive block of the main shaft of the current-assisted friction stir processing equipment; before starting the processing, the argon gas bottle is opened to allow the argon gas to flow into the argon protective cover along the pipeline, and the air in the protective cover is discharged; when the stirring head device is inserted into the dense block blank, the auxiliary DC power supply device is started to form a current loop, and the current-assisted friction stir processing equipment is turned on, during which the processing area is ensured to be protected by argon gas. After the processing is completed, the DC power supply is disconnected and the argon gas bottle is closed.
[0066] It should be noted that during the processing, the working pressure of argon gas was 0.5 MPa, and the distance between the gas and the center of the processing area was 20 mm.
[0067] Preferably, during the current-assisted friction stir processing, the stirring head speed ω is selected as 100 r / min, the moving speed υ is selected as 100 mm / min, and the DC current is selected as 100 A.
[0068]
[0069] Where T0 is the temperature of the material caused by the heat generated by the friction between the stirring head and the material, and the unit is K; T m is the melting point of the material, in K, with a value of 1941K; ω is the rotation speed, in r / min; υ is the moving speed, in mm / min; K and α are constants, with values of 0.70 and 0.05 respectively;
[0070]
[0071] Where ΔT is the temperature of the material caused by the heat generated by the Joule heating effect when the current passes through the material, and the unit is K; ρ is the resistivity of the material, and the unit is Ω·m, which is 0.42×10 -6 Ω·m; j is the current density, the unit is A / m 2 ;t p is the current action time, in seconds, and the value is 50 seconds; C Pis the specific heat capacity of the material, in J / (kg·K), and its value is 523J / (kg·K); d is the density of the material, in kg / m 3 , the value is 4500kg / m 3 ;
[0072] Then the peak temperature during current-assisted friction stir processing is:
[0073] T=T0+ΔT=1085K
[0074] The peak temperature satisfies: 873.15K≤T≤1155.15K.
[0075] In this embodiment, a titanium-based composite material reinforced with a micro-nano multi-scale AlCoCrFeNi high entropy alloy having a mass fraction of 10% is successfully prepared through the above steps. The titanium-based composite material prepared in this embodiment is tested by uniaxial tensile test and nanoindentation test. The results are shown in Tables 1 and Figure 1 , Figure 2 As shown, the titanium-based composite material has excellent mechanical properties. Figure 3 This is the SEM image of the micro-nano multi-scale AlCoCrFeNi high entropy alloy reinforced titanium-based composite material prepared in this example.
[0076] Table 1 Mechanical properties of titanium-based composites reinforced by micro-nano multi-scale AlCoCrFeNi high entropy alloys
[0077]
[0078] Example 2
[0079] In this embodiment, pure titanium TA2 is used as the titanium matrix and CoCrFeNi is used as the high entropy alloy reinforcement particles to prepare a micro-nano multi-scale CoCrFeNi high entropy alloy reinforced titanium-based composite material with a mass fraction of 10%. The specific steps are as follows:
[0080] Step 1, weighing a certain weight of pure titanium TA2 and CoCrFeNi high entropy alloy reinforced particles, so that the mass fraction ratio of pure titanium TA2 and CoCrFeNi high entropy alloy reinforced particles is 9:1, then placing the pure titanium TA2 and CoCrFeNi high entropy alloy reinforced particles in a ball mill for ball milling mixing, the mass ratio of the grinding body to the powder is 5:1, the tank filling rate is 40%, the rotation speed is 150rpm, and the ball milling time is 5h to obtain a mixed powder;
[0081] Step 2, using cold isostatic pressing technology to make the mixed powder obtained in step 1 into a block blank with a size of 200mm×100mm×3mm, using a segmented pressurization and pressure-maintaining method.
[0082] Specifically, the first step: pressurizing time is 30s, maintaining pressure at 30Mpa, supplementing pressure at 20Mpa, and holding pressure for 20min; the second step: pressurizing time is 60s, maintaining pressure at 50Mpa, supplementing pressure at 40Mpa, and holding pressure for 20min; the third step: pressurizing time is 90s, maintaining pressure at 80Mpa, supplementing pressure at 70Mpa, and holding pressure for 20min; the fourth step: pressurizing time is 120s, maintaining pressure at 100Mpa, supplementing pressure at 90Mpa, and holding pressure for 20min.
[0083] Step 3, hot isostatic pressing is used to further eliminate the pores of the block blank obtained in step 2, and a metal container made of stainless steel is used to hermetically package the block blank; the packaged blank is placed in the equipment, and the temperature is gradually increased to 850°C; at the same time, argon gas is injected into the cavity and the pressure is applied to 120Mpa, and the insulation time is maintained for 2 hours to ensure diffusion bonding between particles and pore closure; after the insulation is completed, the temperature is reduced by 30°C / min, and the pressure relief rate is maintained at 2MPa / min. After cooling to room temperature, the pressure is completely relieved to obtain a highly dense block blank.
[0084] Step 4, in an argon protected atmosphere, the high-density block blank obtained in step 3 is subjected to severe plastic deformation processing using current-assisted friction stir processing technology to obtain a micro-nano multi-scale CoCrFeNi high-entropy alloy reinforced titanium-based composite material with a mass fraction of 10%. The specific steps are the same as those in Example 1.
[0085] Preferably, during the current-assisted friction stir processing, the stirring head speed ω is selected as 80r / min, the moving speed υ is selected as 100mm / min, and the DC current is selected as 50A.
[0086]
[0087] Where T0 is the temperature of the material caused by the heat generated by the friction between the stirring head and the material, and the unit is K; T m is the melting point of the material, in K, with a value of 1941K; ω is the rotation speed, in r / min; υ is the moving speed, in mm / min; K and α are constants, with values of 0.70 and 0.05 respectively;
[0088]
[0089] Where ΔT is the temperature of the material caused by the heat generated by the Joule heating effect when the current passes through the material, and the unit is K; ρ is the resistivity of the material, and the unit is Ω·m, which is 0.42×10 -6 Ω·m; j is the current density, the unit is A / m 2 ;t pis the current action time, in seconds, and the value is 50 seconds; C P is the specific heat capacity of the material, in J / (kg·K), and its value is 523J / (kg·K); d is the density of the material, in kg / m 3 , the value is 4500kg / m 3 ;
[0090] Then the peak temperature during current-assisted friction stir processing is:
[0091] T=T0+ΔT=1037K
[0092] The peak temperature satisfies: 873.15K≤T≤1155.15K.
[0093] In this embodiment, a titanium-based composite material reinforced with a micro-nano multi-scale CoCrFeNi high entropy alloy having a mass fraction of 10% is successfully prepared through the above steps. The titanium-based composite material prepared in this embodiment is tested by uniaxial tensile test and nanoindentation test. The results are shown in Table 2 and Table 3. Figure 1 , Figure 2 As shown, the titanium-based composite material has excellent mechanical properties. Figure 4 This is the SEM image of the micro-nano multi-scale CoCrFeNi high entropy alloy reinforced titanium-based composite material prepared in this example.
[0094] Table 2 Mechanical properties of micro-nano multi-scale CoCrFeNi high entropy alloy reinforced titanium matrix composites
[0095]
[0096] Example 3
[0097] In this embodiment, pure titanium TA3 is used as the titanium matrix, CoCrFeMnNi is used as the high entropy alloy reinforcement particles, and a micro-nano multi-scale CoCrFeMnNi high entropy alloy reinforced titanium-based composite material with a mass fraction of 10% is prepared. The specific steps are as follows:
[0098] Step 1, weighing a certain weight of pure titanium TA3 and CoCrFeMnNi high entropy alloy reinforced particles, so that the mass fraction ratio of pure titanium TA3 and CoCrFeMnNi high entropy alloy reinforced particles is 9:1, then placing the pure titanium TA3 and CoCrFeMnNi high entropy alloy reinforced particles in a ball mill for ball milling mixing, the mass ratio of the grinding body to the powder is 5:1, the tank filling rate is 40%, the rotation speed is 150rpm, and the ball milling time is 5h to obtain a mixed powder;
[0099] Step 2, using cold isostatic pressing technology to make the mixed powder obtained in step 1 into a block blank with a size of 200mm×100mm×3mm, using a segmented pressurization and pressure-maintaining method.
[0100] Specifically, the first step: pressurizing time is 30s, maintaining pressure at 30Mpa, supplementing pressure at 20Mpa, and holding pressure for 20min; the second step: pressurizing time is 60s, maintaining pressure at 50Mpa, supplementing pressure at 40Mpa, and holding pressure for 20min; the third step: pressurizing time is 90s, maintaining pressure at 80Mpa, supplementing pressure at 70Mpa, and holding pressure for 20min; the fourth step: pressurizing time is 120s, maintaining pressure at 100Mpa, supplementing pressure at 90Mpa, and holding pressure for 20min.
[0101] Step 3, hot isostatic pressing is used to further eliminate the pores of the block blank obtained in step 2, and a metal container made of stainless steel is used to hermetically package the block blank; the packaged blank is placed in the equipment, and the temperature is gradually increased to 800°C; at the same time, argon is injected into the cavity and the pressure is applied to 100Mpa, and the insulation time is maintained for 2 hours to ensure diffusion bonding between particles and pore closure; after the insulation is completed, the temperature is reduced by 30°C / min, and the pressure relief rate is maintained at 2MPa / min. After cooling to room temperature, the pressure is completely relieved to obtain a highly dense block blank.
[0102] Step 4, in an argon protected atmosphere, the dense block blank obtained in step 3 is subjected to severe plastic deformation processing by current-assisted friction stir processing technology to obtain a micro-nano multi-scale CoCrFeMnNi high-entropy alloy reinforced titanium-based composite material with a mass fraction of 10%. The specific steps are the same as those in Example 1.
[0103] Preferably, during the current-assisted friction stir processing, the stirring head speed ω is selected to be 50 r / min, the moving speed υ is selected to be 100 mm / min, and the DC current is selected to be 150 A.
[0104]
[0105] Where T0 is the temperature of the material caused by the heat generated by the friction between the stirring head and the material, and the unit is K; T m is the melting point of the material, in K, with a value of 1941K; ω is the rotation speed, in r / min; υ is the moving speed, in mm / min; K and α are constants, with values of 0.70 and 0.05 respectively;
[0106]
[0107] Where ΔT is the temperature of the material caused by the heat generated by the Joule heating effect when the current passes through the material, and the unit is K; ρ is the resistivity of the material, and the unit is Ω·m, which is 0.42×10 -6 Ω·m; j is the current density, the unit is A / m 2 ;tp is the current action time, in seconds, and the value is 50 seconds; C P is the specific heat capacity of the material, in J / (kg·K), and its value is 523J / (kg·K); d is the density of the material, in kg / m 3 , the value is 4500kg / m 3 ;
[0108] Then the peak temperature during current-assisted friction stir processing is:
[0109] T=T0+ΔT=1024K
[0110] The peak temperature satisfies: 873.15K≤T≤1155.15K.
[0111] In this embodiment, a titanium-based composite material reinforced with a micro-nano multi-scale CoCrFeMnNi high entropy alloy having a mass fraction of 10% is successfully prepared through the above steps. The titanium-based composite material prepared in this embodiment is tested by uniaxial tensile test and nanoindentation test. The results are shown in Table 3 and Table 4. Figure 1 , Figure 2 As shown, the titanium-based composite material has excellent mechanical properties. Figure 5 This is the SEM image of the micro-nano multi-scale CoCrFeMnNi high-entropy alloy reinforced titanium-based composite material prepared in this example.
[0112] Table 3 Mechanical properties of micro-nano multi-scale CoCrFeMnNi high entropy alloy reinforced titanium matrix composites
[0113]
[0114] Example 4
[0115] In this embodiment, pure titanium TA1 is used as the titanium matrix, CoCrFeMnNi is used as the high entropy alloy reinforcement particles, and a micro-nano multi-scale CoCrFeMnNi high entropy alloy reinforced titanium-based composite material with a mass fraction of 10% is prepared. The specific steps are as follows:
[0116] Step 1, weighing a certain weight of pure titanium TA1 and CoCrFeMnNi high entropy alloy reinforcement particles, so that the mass fraction ratio of CoCrFeMnNi high entropy alloy powder to pure titanium TA1 powder is 1:9, and then placing the two powders in a ball mill for ball milling mixing, the mass ratio of the grinding body to the powder is 5:1, the tank filling rate is 40%, the rotation speed is 150rpm, and the ball milling time is 5h to obtain a mixed powder;
[0117] Step 2, using cold isostatic pressing technology to make the mixed powder obtained in step 1 into a block blank with a size of 200mm×100mm×3mm, using a segmented pressurization and pressure-maintaining method.
[0118] Specifically, the first step: pressurizing time is 30s, maintaining pressure at 30Mpa, supplementing pressure at 20Mpa, and holding pressure for 20min; the second step: pressurizing time is 60s, maintaining pressure at 50Mpa, supplementing pressure at 40Mpa, and holding pressure for 20min; the third step: pressurizing time is 90s, maintaining pressure at 80Mpa, supplementing pressure at 70Mpa, and holding pressure for 20min; the fourth step: pressurizing time is 120s, maintaining pressure at 100Mpa, supplementing pressure at 90Mpa, and holding pressure for 20min.
[0119] Step 3, hot isostatic pressing is used to further eliminate the pores of the block blank obtained in step 3, and a metal container made of stainless steel is used to hermetically package the block blank; the packaged blank is placed in the equipment, and the temperature is gradually increased to 780°C; at the same time, argon is injected into the cavity and the pressure is applied to 100Mpa, and the insulation time is maintained for 2.5 hours to ensure diffusion bonding between particles and pore closure; after the insulation is completed, the temperature is reduced by 30°C / min, and the pressure relief rate is maintained at 2MPa / min. After cooling to room temperature, the pressure is completely relieved to obtain a highly dense block blank.
[0120] Step 4, in an argon protected atmosphere, the dense block blank obtained in step 3 is subjected to severe plastic deformation processing by current-assisted friction stir processing technology to obtain a titanium-based composite material reinforced with a micro-nano multi-scale CoCrFeMnNi high-entropy alloy with a mass fraction of 10%. The specific steps are the same as those in Example 1.
[0121] Preferably, during the current-assisted friction stir processing, the stirring head speed ω is selected to be 40r / min, the moving speed υ is selected to be 120mm / min, the DC current is 200A, and the
[0122]
[0123] Where T0 is the temperature of the material caused by the heat generated by the friction between the stirring head and the material, and the unit is K; T m is the melting point of the material, in K, with a value of 1941K; ω is the rotation speed, in r / min; υ is the moving speed, in mm / min; K and α are constants, with values of 0.70 and 0.05 respectively;
[0124]
[0125] Where ΔT is the temperature of the material caused by the heat generated by the Joule heating effect when the current passes through the material, and the unit is K; ρ is the resistivity of the material, and the unit is Ω·m, which is 0.42×10 -6 Ω·m; j is the current density, the unit is A / m 2 ;tp is the current action time, in seconds, and the value is 50 seconds; C P is the specific heat capacity of the material, in J / (kg·K), and its value is 523J / (kg·K); d is the density of the material, in kg / m 3 , the value is 4500kg / m 3 ;
[0126] Then the peak temperature during current-assisted friction stir processing is:
[0127] T=T0+ΔT=1038K
[0128] The peak temperature satisfies: 873.15K≤T≤1155.15K.
[0129] In this embodiment, a titanium-based composite material reinforced with a micro-nano multi-scale CoCrFeMnNi high entropy alloy having a mass fraction of 10% is successfully prepared through the above steps. The titanium-based composite material prepared in this embodiment is tested by uniaxial tensile test and nanoindentation test. The results are shown in Table 4. The titanium-based composite material has excellent mechanical properties. Figure 6 This is the SEM image of the micro-nano multi-scale CoCrFeMnNi high-entropy alloy reinforced titanium-based composite material prepared in this example.
[0130] Table 4 Mechanical properties of micro-nano multi-scale CoCrFeMnNi high entropy alloy reinforced titanium matrix composites
[0131]
[0132] Comparative Example 1
[0133] In this comparative example, pure titanium TA1 is used as the titanium matrix and AlCoCrFeNi is used as the high entropy alloy reinforcement particles to prepare a 10% mass fraction of micro-nano multi-scale AlCoCrFeNi high entropy alloy reinforced titanium matrix composite material. The difference is that the peak temperature reached by the material in this comparative example is higher than 1155.15K, which exceeds the phase transition temperature of pure titanium. The specific steps are as follows:
[0134] Step 1, weighing a certain weight of pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles, so that the mass fraction ratio of pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles is 9:1, and then placing the pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles in a ball mill for ball milling mixing, the mass ratio of balls to powder is 5:1, the tank filling rate is 40%, the rotation speed is 150rpm, and the ball milling time is 5h to obtain a mixed powder;
[0135] Step 2, using cold isostatic pressing technology to make the mixed powder obtained in step 1 into a block blank with a size of 200mm×100mm×3mm, using a segmented pressurization and pressure-maintaining method.
[0136] Specifically, the first step: the pressure time is 30s, the pressure is maintained at 30Mpa, the additional pressure is 20Mpa, and the pressure holding time is 20min; the second step: the pressure time is 60s, the pressure is maintained at 50Mpa, the additional pressure is 40Mpa, and the pressure holding time is 20min; the third step: the pressure time is 90s, the pressure is maintained at 80Mpa, the additional pressure is 70Mpa, and the pressure holding time is 20min; the fourth step: the pressure time is 120s, the pressure is maintained at 100Mpa, the additional pressure is 90Mpa, and the pressure holding time is 20min;
[0137] Step 3, hot isostatic pressing is used to further eliminate the pores of the block blank obtained in step 2, and a metal container made of stainless steel is used to hermetically package the block blank; the packaged blank is placed in the equipment, and the temperature is gradually increased to 800°C; at the same time, argon is injected into the cavity and the pressure is applied to 100Mpa, and the insulation time is maintained for 2 hours to ensure diffusion bonding between particles and pore closure; after the insulation is completed, the temperature is reduced by 30°C / min, and the pressure relief rate is maintained at 2MPa / min. After cooling to room temperature, the pressure is completely relieved to obtain a highly dense block blank.
[0138] Step 4, in an argon protected atmosphere, the high-density block blank obtained in step 3 is subjected to severe plastic deformation processing using current-assisted friction stir processing technology to obtain a micro-nano multi-scale AlCoCrFeNi high-entropy alloy reinforced titanium-based composite material with a mass fraction of 10%. The specific steps are the same as those in Example 1.
[0139] In the current-assisted friction stir processing, the stirring head speed ω is selected as 200r / min, the moving speed υ is selected as 50mm / min, and the DC current is selected as 300A.
[0140]
[0141] Where T0 is the temperature of the material caused by the heat generated by the friction between the stirring head and the material, and the unit is K; T m is the melting point of the material, in K, with a value of 1941K; ω is the rotation speed, in r / min; υ is the moving speed, in mm / min; K and α are constants, with values of 0.70 and 0.05 respectively;
[0142]
[0143] Where ΔT is the temperature of the material caused by the heat generated by the Joule heating effect when the current passes through the material, and the unit is K; ρ is the resistivity of the material, and the unit is Ω·m, which is 0.42×10 -6 Ω·m; j is the current density, the unit is A / m 2 ;t p is the current action time, in seconds, and the value is 50 seconds; C P is the specific heat capacity of the material, in J / (kg·K), and its value is 523J / (kg·K); d is the density of the material, in kg / m 3 , the value is 4500kg / m 3 ;
[0144] Then the peak temperature during current-assisted friction stir processing is:
[0145] T=T0+ΔT=1303K
[0146] Peak temperature T>1155.15K.
[0147] The comparative example successfully prepared a micro-nano multi-scale AlCoCrFeNi high entropy alloy reinforced titanium-based composite material with a mass fraction of 10% through the above steps. The titanium-based composite material prepared in this comparative example was tested by uniaxial tensile test and nanoindentation test. The results are shown in Table 5. The mechanical properties of the titanium-based composite material are significantly reduced compared with the above embodiment. The main reasons are that the peak temperature is high, the grains are abnormally coarsened, and the phase change of pure titanium at high temperature leads to uneven microstructure of the material, which reduces the mechanical properties of the material.
[0148] Table 5 Mechanical properties of titanium matrix composites reinforced with 10 vol% AlCoCrFeNi high entropy alloy
[0149]
[0150] Comparative Example 2
[0151] This comparative example is to prepare a titanium-based composite material without forming a micro-nano multi-scale high entropy alloy reinforcement, and the specific steps are as follows:
[0152] Step 1, weighing a certain weight of pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles, so that the mass fraction ratio of pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles is 9:1, then placing the pure titanium TA1 and AlCoCrFeNi high entropy alloy reinforced particles in a ball mill for ball milling mixing, the mass ratio of the grinding body to the powder is 5:1, the tank filling rate is 40%, the rotation speed is 150rpm, and the ball milling time is 5h to obtain a mixed powder;
[0153] Step 2, using cold isostatic pressing technology to make the mixed powder obtained in step 1 into a block blank with a size of 200mm×100mm×3mm, using a segmented pressurization and pressure-maintaining method.
[0154] Specifically, the first step: pressurizing time is 30s, maintaining pressure at 30Mpa, supplementing pressure at 20Mpa, and holding pressure for 20min; the second step: pressurizing time is 60s, maintaining pressure at 50Mpa, supplementing pressure at 40Mpa, and holding pressure for 20min; the third step: pressurizing time is 90s, maintaining pressure at 80Mpa, supplementing pressure at 70Mpa, and holding pressure for 20min; the fourth step: pressurizing time is 120s, maintaining pressure at 100Mpa, supplementing pressure at 90Mpa, and holding pressure for 20min; that is, a micron-level high-entropy alloy reinforced titanium-based composite material is obtained.
[0155] Step 3, hot isostatic pressing is used to further eliminate the pores of the block blank obtained in step 2, and a metal container made of stainless steel is used to hermetically package the block blank; the packaged blank is placed in the equipment, and the temperature is gradually increased to 800°C; at the same time, argon is injected into the cavity and the pressure is applied to 100Mpa, and the insulation time is maintained for 2 hours to ensure diffusion bonding between particles and pore closure; after the insulation is completed, the temperature is reduced by 30°C / min, and the pressure relief rate is maintained at 2MPa / min. After cooling to room temperature, the pressure is completely relieved to obtain a highly dense block blank.
[0156] The titanium-based composite material prepared in this comparative example was tested by uniaxial tensile test and nanoindentation test. The results are shown in Table 6. The mechanical properties of the micron-sized high entropy alloy reinforced titanium-based composite material are significantly reduced compared with the above-mentioned embodiment.
[0157] Table 6 Mechanical properties of micron-sized high entropy alloy reinforced titanium matrix composites
[0158]
[0159] Comparative Example 3
[0160] Chinese patent CN114058983A uses ceramic particles such as TiBxCy as reinforcement to prepare titanium-based composite materials with a tensile strength of 770MPa and an elongation of 19%. Compared with titanium-based composite materials prepared with traditional ceramic particles as reinforcement, the mechanical properties of the micro-nano multi-scale high entropy alloy reinforced titanium-based composite materials prepared by the present invention have been significantly improved.
[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A micro-nano multi-scale high entropy alloy reinforced titanium-based composite material, characterized in that: It includes a titanium matrix and micro-nano multi-scale high entropy alloy reinforcement particles, wherein the micro-nano multi-scale high entropy alloy reinforcement particles include micron-scale and nano-scale high entropy alloy reinforcement particles; The micron-sized high entropy alloy reinforcement particles are added through the original powder; The nano-scale high entropy alloy reinforcement particles are formed by mechanical crushing during ball milling and current-assisted friction stir processing; The micron-sized high entropy alloy reinforcement particles form a continuous and complete interface bond with the titanium matrix, thereby forming a core-shell structure.
2. The micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 1, characterized in that: The titanium matrix is one of TA1, TA2 or TA3 industrial pure titanium, and the high entropy alloy reinforcement particles are one of CoCrFeNi, CoCrFeMnNi or AlCoCrFeNi high entropy alloys.
3. The micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 1, characterized in that: The particle size distribution range of the titanium matrix and the high entropy alloy reinforcement particles is 13-53 μm, and the purity is ≥99%.
4. A method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, weighing a certain weight of titanium matrix powder and high entropy alloy reinforced particle powder, and then placing the two powders in a ball mill for ball milling and mixing to obtain a mixed powder; Step 2, using cold isostatic pressing technology to make the mixed powder into a block billet by using a segmented pressurization and pressure holding method, and then using hot isostatic pressing technology to obtain a high-density block billet; Step 3: In a protective atmosphere, the high-density block blank is plastically deformed by using current-assisted friction stir processing technology to obtain a micro-nano multi-scale high-entropy alloy reinforced titanium-based composite material.
5. The method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 4, characterized in that: The mass fraction ratio of the titanium matrix and the high entropy alloy reinforcement particles is 9:
1.
6. The micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 4, characterized in that: During the ball milling and mixing, the mass ratio of the grinding body to the powder is 3:1-10:1, the tank filling rate is 30%-50%, the rotation speed is 90rpm-300rpm, and the ball milling time is 3h-6h.
7. The method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 4, characterized in that: The cold isostatic pressing technology uses rubber as the material for the encapsulation mold, and the pressure medium is a liquid mixed with distilled water and emulsion; The method of stepwise pressurization and pressure maintenance specifically comprises the following steps: Step 1: Apply pressure for 30 seconds, maintain pressure at 30 MPa, add 20 MPa of additional pressure, and hold pressure for 20 minutes; Step 2: Pressurization time is 60s, maintaining pressure at 50Mpa, supplementary pressure at 40Mpa, and holding time is 20min; Step 3: Pressurize for 90 seconds, maintain pressure at 80 MPa, add 70 MPa, and hold pressure for 20 minutes; Step 4: Apply pressure for 120s, maintain pressure at 100Mpa, add pressure at 90Mpa, and hold pressure for 20min.
8. The method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 4, characterized in that: The hot isostatic pressing technology uses argon as the pressure transmission medium, the processing temperature is 700-850°C, the working pressure is 100-150Mpa, the insulation time is 2-4 hours, the cooling rate is 20-50°C / min, and the pressure relief rate is 1-5MPa / min.
9. The method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 4, characterized in that: The protective atmosphere is argon gas, the gas working pressure is 0.2-1.0 MPa, the distance between the gas and the center of the processing area is 10-30 mm, and the gas concentration is ≥99%.
10. The method for preparing a micro-nano multi-scale high entropy alloy reinforced titanium-based composite material according to claim 4, characterized in that: The current of the current-assisted friction stir processing technology is a direct current of 50-200A, and the current source is a high-frequency switching direct current power supply; during the current-assisted friction stir processing, the peak temperature range is 873.15K≤T≤1155.15K.
Citation Information
Patent Citations
Particle-reinforced titanium-based composite material and preparation process thereof
CN114058983A
Cited By
Titanium-based composite part and preparation method and application thereof
CN119973111A